System of mode variables of energy circuits - Muzychak, Andriy (Publishing House of Lviv Polytechnic National University, 2015)
Modern energy systems feature diversity of elements and combination of processes and phenomena of various physical natures. Mathematical modelling of such systems relies on the tools of the theory of energy circuits. One of the major problems of this theory is formation of the unified system of interrelated variables which allow describing phenomena in circuits of various physical natures. Such a system of variables is underlain by the principle of energy analogy, which is based on the fundamental law of nature - the law of conservation of energy. The relationship between the variables is substantiated on the example of a mechanical circuit, since in mechanics both potential and kinetic energy are most illustrative. Results obtained for a echanical circuit were then applied to circuits of other physical natures. Energy of magnetic field of the inductor is a counterpart of kinetic energy; therefore, kinetic energy in a mechanical circuit can be defined using generalized inductance. Correspondingly, energy of electrostatic field of the capacitor is a counterpart of potential energy, due to which potential energy in a mechanical circuit can be defined through generalized capacitance. Сучасні енергетичні системи характеризуються розмаїттям елементів та поєднанням у них процесів і явищ різної фізичної природи. Інструментом математичного моделювання таких систем є апарат теорії енергетичних кіл. Однією з важливих проблем цієї теорії є утворення єдиної системи взаємозв’язаних зм нних, що дають змогу описати явища в колах різної фізичної природи. В основі побудови такої системи змінних покладено принцип енергетичної аналогії, який основується на фундаментальному законі природи – законі збереження енергії. Взаємозв’язок між змінними обґрунтовано на прикладі механічного кола, оскільки саме в механіці найнаочнішими є обидві форми енергії – кінетична та потенціальна. Результати, отримані для механічного кола, поширено на кола іншої фізичної природи. Енергія магнітного поля індуктивності є аналогом кінетичної форми енергії, відповідно кінетичну енергію у механічному колі можна визначати через узагальнену індуктивність; а енергія електростатичного поля конденсатора – аналогом потенціальної форми енергії, відповідно потенціальну енергію у механічному колі можна визначати через узагальнену ємність.
Система змінних режиму енергетичних кіл
Keywords: energy circuit; metric and energy analogy; power; kinetic and potential energy; енергетичне коло; метрична й енергетична аналогія; потужність; кінетична та потенціальна форми енергії